Roles of Chronic Low-Grade Inflammation in the Development of Ectopic Fat Deposition - Lulu Liu; Mei Mei; Shumin Yang; Qifu Li (Mediators of Inflammation)
Pattern of fat distribution is a major determinant for metabolic homeostasis. As a depot of energy, the storage of triglycerides in adipose tissue contributes to the normal fat distribution. Decreased capacity of fat storage in adipose tissue may result in ectopic fat deposition in nonadipose tissues such as liver, pancreas, and kidney. As a critical biomarker of metabolic complications, chronic low-grade inflammation may have the ability to affect the process of lipid accumulation and further lead to the disorder of fat distribution. In this review, we have collected the evidence linking inflammation with ectopic fat deposition to get a better understanding of the underlying mechanism, which may provide us with novel therapeutic strategies for metabolic disorders.